Bibliometric Insights Into the Open Education Landscape - Zou, Rong; Jiang, Leilei; Wider, Walton (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
This bibliometric analysis explores the rapidly growing field of open education, offering insight into its nature and the wide range of academic topics it covers. This study applies co-citation and co-word analyses approach to critically review 402 publications from the Web of Science database. The aim is to identify emerging topics, seminal works, and dominant trends in the literature on open education. The co-citation analysis identifies key publications and thematic clusters that define the field, including discussions on pedagogical innovations, equity and accessibility, quality assurance, and the global impact of open educational practices (OEP). Co-word analysis, on the other hand, highlights the recurrent and emerging keywords within the literature, revealing focal points such as digital transformation in education, the role of massive open online courses (MOOCs), and the significance of open educational resources (OER) in fostering inclusive and equitable learning environments. This study stands out for its quantitative approach in mapping the current academic conditions of open education, offering insights into the dynamic interplay between technology, policy, and pedagogy. It emphasizes the need for a collaborative, inclusive approach to education, employing open educational resources and methods to fulfill the different needs of learners globally. Through this analysis, the study contributes to a deeper understanding of the current state and future directions of open education, advocating for policies and practices that support sustainable, accessible, and high-quality educational experiences.